The Mediating Role of Corporate Governance in the Relationship between Net Profit and Equity and Voluntary Disclosure in the Context of Legitimacy Theory - Gezgin, Talha; Özer, Gökhan; Merter, Abdullah Kursat; Balcioglu, Yavuz Selim (Mdpi, 2024)
Amidst ongoing global economic and environmental crises, the concept of legitimacy has gained paramount importance for firms, which must not only survive but also maintain their legitimacy through comprehensive disclosures. This study investigates the mediating role of corporate governance in shaping firm performance and voluntary disclosure, emphasizing sustainability implications. Analyzing 82 firms across various sectors in Turkey from 2010 to 2020, the research reveals no direct relationship between corporate governance and equity. However, it identifies a partial mediation effect of corporate governance on the disclosure of general, strategic, and forward-looking financial information related to net profit. Critically, our findings demonstrate that corporate governance fully mediates the relationship between net profit and the disclosure of social and board information, with the magnitude of this indirect effect being complete. This underscores the fact that robust corporate governance enhances transparency in social and environmental reporting, thereby supporting firms in their efforts to align with sustainable business practices and stakeholder expectations. These results highlight the crucial role of effective governance in ensuring comprehensive disclosures that support the sustainability goals of modern enterprises.
Keywords: legitimacy theory; corporate governance; firm performance; voluntary disclosure; structural equation modelling; SEM